2017
DOI: 10.1063/1.4973968
|View full text |Cite
|
Sign up to set email alerts
|

Generalized approach to design multi-layer stacks for enhanced optical detectability of ultrathin layers

Abstract: The optical detectability of ultrathin conductive films (down to one atomic layer) can be enhanced by choosing distinct layer-stacks. A simple analytical approach using the transfer matrix method is applied for calculating the reflectance of arbitrary multi-layer stack systems with and without the ultrathin layer of interest on top in a wide wavelength range, including both the visible spectrum and the ultraviolet spectrum. Then, the detectability defined by the Michelson contrast was calculated. Performing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Immerse the PMMA-coated graphene in a Petri dish filled with DI water (Figure 3a). NOTE: The number of layers of graphene can be determined using feasible techniques 32,33 . 2.…”
Section: Transfer Of Graphene Onto Tem Gridsmentioning
confidence: 99%
“…Immerse the PMMA-coated graphene in a Petri dish filled with DI water (Figure 3a). NOTE: The number of layers of graphene can be determined using feasible techniques 32,33 . 2.…”
Section: Transfer Of Graphene Onto Tem Gridsmentioning
confidence: 99%
“…With the optical system being accurately described, different 2D materials in Van-der-Waals heterostructures can be discriminated while simultaneously determining their number of layers by combining both mentioned evaluation schemes, i.e. the contrast-based 5 (in this particular case absolute reflectance instead of contrast is deployed) and the wavelength-shift based method 8 . The applicability of this strategy is demonstrated for the extreme case of graphene-hBN heterostructures, where the influence of individual layers on reflected light is weak due to their extraordinary small thickness (graphene: 3.35 Å 2 ; hBN: 3.33 Å 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Optical spectroscopy is used for characterizing ultra-thin films down to atomic layers. It has been shown that in particular reflectance spectroscopy is well-suited for detecting single atomic layers of 2D materials like graphene (Gr) [1][2][3][4][5][6] , hexagonal boron nitride (hBN) 3,7,8 or transition metal dichalcogenides (TMD) 3,[8][9][10] like MX2 (M = Mo, W; X = S, Se, Te). For this purpose, reflectance spectra of a dielectric layer stack in combination with a superimposed ultra-thin layer are acquired and the deviation between both reflectance spectra is evaluated in form of contrast spectra 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations